The use of semen evaluation and assisted reproduction in Spix's macaws in terms of species conservation. Issue 3 (19th April 2014) - Fischer, Dominik; Neumann, Daniel; Purchase, Cromwell; Bouts, Tim; Meinecke‐Tillmann, Sabine; Wehrend, Axel; Lierz, Michael
<x xml:space="preserve">Abstract</x> The Spix's macaw (Cyanopsitta spixii) is the rarest parrot on earth. The remaining captive population consists of 79 individuals. Captive propagation is ongoing to increase the number of individuals for future reintroduction back into the wild. Unfortunately, from 2004 to 2012, only 33 chicks hatched from 331 eggs. Semen evaluation and assisted reproduction might help to overcome this problem. Therefore, a recently developed electro‐stimulated semen collection technique was used in Spix's macaws. Semen collection was successful in 39 of 78 attempts in 10 out of 17 males. Examination of the semen included evaluation of volume, color, consistency, contaminations and pH, as well as determination of motility, viability, morphology, concentration, and total count of spermatozoa. The median volume of semen samples was 5.6 µl. On average, 34.7 ± 21.9% (median 30%) of the sperm were motile and 23.1 ± 22.1% (median 16.5%) were progressively motile. In addition to spermatozoa, round cells were detected in the samples. Median sperm concentration was 15, 500/µl (range 500–97, 500/µl) and median viability was 50% (range 5–87%). Morphological examination revealed in 26.5% normal spermatozoa, high numbers of malformations of the head (50.2%) and tail region (20.5%), with 29% of all sperm showing multiple abnormalities. Artificial insemination was performed in three females; two eggs laid after artificial insemination had spermatozoa present on the perivitelline layer, suggesting the possible success of the insemination technique. Although no fertilization could be demonstrated, these preliminary results are promising, as they indicate that assisted reproduction might be a tool for species conservation in the Spix's macaw. Zoo Biol. 33:234–244, 2014. © 2014 Wiley Periodicals Inc.